18F-fluorodeoxyglucose positron emission tomography computed tomography (18F-PET/CT) for the diagnosis of native valve infective endocarditis (NVIE): a prospective study. (25th November 2020) - Philip, M; Delcourt, S; Cammilleri, S; Gourriet, F; Tessonnier, L; Casalta, J.P; Gardenat, A; Gerard, H; Riberi, A; Hubert, S; Habib, G
Abstract: Background and objectives: 18F-FDG PET/CT has recently been added as a major criterion in the ESC 2015 infective endocarditis (IE) guidelines. We and others have demonstrated that18F-fluorodeoxyglucose (FDG) positron emission tomography (PET) / computed tomography (CT) was useful in patients with suspected prosthetic valve and cardiac device IE. However, the sensitivity and specificity of ESC classification is unknown in patients with native valve endocarditis (NVE) as well as the clinical impact of PET findings. Purposes: 1. Primary objective: To assess the value of the new ESC criteria including 18F-FDG PET/CT in native valve infective endocarditis (NVIE). 2. Secondary objectives: – to determine the usefulness of PET/CT concerning embolic or neoplastic detection. – to describe a new PET/CT feature, i.e. the diffuse splenic uptake. Methods: Between 2012 and 2017, 75 patients with suspected NVIE were prospectively included, after exclusion of patients with uninterpretable or not feasible PET/CT. Using the expert consensus of the Endocarditis Team after a 3-month follow-up as gold standard, 63 IE were confirmed and 12 were rejected. Patients follow-up was scheduled at one and three months after hospitalization. Results: Significant cardiac uptake by PET/CT (major criterion) was observed in 11 among 63 patients with definite NVIE and no patients with rejected IE (sensitivity 18%, specificity 100%). Among the 63 patients with a final diagnosis of NVE, a peripheral embolism or mycotic aneurysm was observed in 20 cases (32%). Considering this, the ESC 2015 classification increased the sensitivity of Duke criteria from 64 to 70% (p<0.001) without no change on specificity (p<0.001). Twenty-four patients (38%) were diagnosed with secondary infectious sites or infectious portal of entry. A diffuse splenic uptake was observed in 39 (52%) patients, including 37 (59%) of patients with a final diagnosis of NVE (specificity 83%). Conclusion: 1. The value of 18F-FDG PET/CT in NVE diagnosis is poor (18% sensitivity) 2. Usefulness of PET/CT remains high when concerning embolic or neoplastic detection. 3. Our study describes for the first time in NVE a new potential endocarditis criterion, i.e. the presence of a diffuse splenic uptake on 18F-FDG PET/CT Funding Acknowledgement: Type of funding source: None